Long-term population trends of introduced mammals on an tropical island - Haji, Júlio [UNESP]; Ferreguetti, Atilla; Bovendorp, Ricardo S. [UNESP]; Bueno, Rafael S. [UNESP]; Gonçalves, Fernando [UNESP]; Galetti, Mauro [UNESP] (Elsevier, 2023)
The introduction of species in areas with no top-down control is a recipe for ecosystem catastrophe. Theory predicts that introduced species in areas that lack predators may experience rapid growth and subsequently crash or stabilize around the carrying capacity. Impressively, there are very few studies on the population trend of tropical forest-dwelling mammals. In 1983, 100 individuals from 15 species of generalist mammals were introduced on an 828-ha tropical island in Southeast Brazil (Anchieta Island). Here, we present the status and population dynamics of the introduced species after 19, 21, 35, 38, and 39 years based on 611 km of line transects split into diurnal and nocturnal surveys. Among the introduced species, five were extinct and two species became super-abundant. The population of agouti has been fluctuating around 900 individuals and black-tufted marmoset around 600 individuals which may reflect the carrying capacity of the island. Our results showed that a tropical island, without top predators, resulted in a massive population explosion of 2 of the 15 introduced mammals, demonstrating that colonization and invasion processes are not straightforward to predict.
Keywords: Atlantic forest; Biological invasion; Capuchin monkeys; Coatis; Distance sampling; Line transect; Parque Estadual Ilha Anchieta